Diet and ideal food pyramid to prevent or support the treatment of diabetic retinopathy, age-related macular degeneration, and cataracts - Rondanelli, Mariangela; Gasparri, Clara; Riva, Antonella; Petrangolini, Giovanna; Barrile, Gaetan Claude; Cavioni, Alessandro; Razza, Claudia; Tartara, Alice; Perna, Simone (Frontiers in Medicine, 2023)
Many eye diseases, such as Diabetic Retinopathy (DR), Age-Related Macular degeneration (AMD) and Cataracts are preventable and treatable with lifestyle. The objective of this review is to assess the most recent research on the ideal dietary approach to prevent or support the treatment of DR, AMD, and cataracts, as well as to construct a food pyramid that makes it simple for people who are at risk of developing these pathologies to decide what to eat. The food pyramid presented here proposes what should be consumed everyday: 3 portions of low GI grains (for fiber and zinc content), 5 portions (each portion:≥200 g/day) of fruits and vegetables (spinach, broccoli, zucchini cooked, green leafy vegetables, orange, kiwi, grapefruit for folic acid, vitamin C, lutein/zeaxanthin content, at least ≥42 µg/day, are to be preferred), extra virgin olive oil (almost 20 mg/day for vitamin E, polyphenols content), nuts or oil seeds (20-30g/day, for zinc content, at least ≥15.8mg/day); weekly: fish (4 portions, for omega-3 content, EPA+DHA 0.35-1.4g/day), white meat (3 portions for vitamin B12 content), legumes (2 portions for vegetal proteins), eggs (2 portions for lutein/zeaxanthin content), light cheeses (2 portions for vitamin B6 content), almost three-four/times/week microgreen and spices (saffron and curcumin). At the top of the pyramid, there are two pennants: one green, which indicates the need for personalized supplementation (if daily requirements cannot be met through diet, omega-3 and L-methylfolate supplementation), and one red, which indicates that certain foods are prohibited (salt and sugar). Finally, 3-4 times per week, 30-40 minutes of aerobic and resistance exercises are required.